EOSINOPHILIC GASTRITIS; AN UNUSUAL AND OVERLOOKED CAUSE OF CHRONIC ABDOMINAL PAIN - Ayyub, Muhammad; Almenawi, Lubna; Mogharbel, Mohammad Hussain (Journal of Ayub Medical College Abbottabad, 2007)
Eosinophilic gastritis is an extremely rare disorder. The disease is associated with eosinophilic infiltration of various layers of gastrointestinal tract along with significant peripheral eosinophilia and increased Immunoglobulin E (IgE). We report a case of 37 year old Saudi male who presented with chronic non-specific upper abdominal pain. On initial workup, the diagnosis was missed. However the diagnosis was established after subsequent work up in Gastroenterology clinic. Our case demonstrates that patients with uncharacteristic abdominal pain who are unresponsive to conventional treatment, rare illnesses like eosinophilic gastritis should be considered. We also aim to review the clinicopathological features, differential diagnosis and various treatment options of this disorder. To the best of our knowledge, this disease has not been previously reported from Saudi Arabia. Keywords: Eosinophilic Gastritis; Eosinophilia; Atopy; Food Allergy; Bronchial Asthma; Abdominal pain